The role of naloxegol in the management of opioid-induced bowel dysfunction - Leppert, Wojciech; Woron, Jaroslaw (Therapeutic advances in gastroenterology, 2016)
Opioid-induced constipation (OIC) and other gastrointestinal (GI) symptoms of opioid-induced bowel dysfunction (OIBD) significantly deteriorate patients’ quality of life and may lead to noncompliance with opioid schedule and undertreatment of pain. Although traditional oral laxatives are the first-line treatment of OIC, they do not address OIBD pathophysiology, and display numerous adverse effects. OIC treatment includes prokinetics (lubiprostone), opioid switch, and changing route of opioid administration. Targeted management of OIBD comprises the use of purely peripherally acting μ-opioid receptor antagonists (PAMORA): naloxegol and methylnaltrexone. Naloxegol (NKTR-118) is a polymer conjugate of the opioid antagonist naloxone. The polyethylene glycol limits naloxegol capacity to cross the blood–brain barrier (BBB). Naloxegol is substrate for the P-glycoprotein (P-gp) transporter. The central nervous system penetration of naloxegol is negligible due to reduced permeability and its increased efflux across the BBB, related to P-gp transporter. Naloxegol antagonizes μ- and κ-opioid receptors and displays low affinity to δ-opioid receptors in the GI tract, thereby decreasing OIBD symptoms without reversing central analgesic effects. Naloxegol is metabolised through CYP3A4 to six metabolites, with the majority of the dose (68%) excreted with faeces and less (16%) with urine. The dose of naloxegol equals 25 mg administered orally once daily on a fasting condition. Mild or moderate hepatic impairment has no impact on naloxegol dosing; naloxegol was not studied and is not recommended in patients with hepatic failure. Dose reduction (12.5 mg once daily) and caution is recommended in patients with moderate-to-severe renal impairment. Efficacy (bowel movement in 42–49% of patients not responsive to laxatives) and safety of naloxegol were confirmed in studies conducted in patients with OIC and nonmalignant pain. Naloxegol may be useful for cancer patients with OIC, although studies in this population are lacking.